2018
DOI: 10.1177/0021998318820422
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of recycled carbon fiber-based binder tapes for automated tape laying processes

Abstract: The current growth in use of fiber reinforced polymer composites causes a strongly increasing amount of waste. Current approaches for fiber reinforced polymer composites recycling usually not exploit the potential of endless fibers as they are shortened during recycling and will not be properly aligned in the final product. Considering this, the present work aimed at the development of a recycling process for long recycled carbon fibers, where fiber length is preserved and load-related fiber orientation is pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Throughout these processes, careful consideration of applied forces must be made to ensure that the fiber length does not degrade to an unacceptable extent. The unspun slivers can be used to produce non-crimp fabrics [26] and tapes [27][28][29] for consolidation via compression molding. The spun yarns can be wrapped around a mandrel [30,31] or woven into fabrics [32,33] for compression molding.…”
Section: Yarn Spinningmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout these processes, careful consideration of applied forces must be made to ensure that the fiber length does not degrade to an unacceptable extent. The unspun slivers can be used to produce non-crimp fabrics [26] and tapes [27][28][29] for consolidation via compression molding. The spun yarns can be wrapped around a mandrel [30,31] or woven into fabrics [32,33] for compression molding.…”
Section: Yarn Spinningmentioning
confidence: 99%
“…They showed that a homogeneous blend was possible with minimal thickness variation and good tensile strength. Rimmel et al [29] at the Institute for Composite Materials in Germany produced highly aligned composites from 150 mm long recycled carbon fibers. The tapes were produced by carding the fibers mixed with PA6 fibers and drawing the web into a sliver.…”
Section: Cardingmentioning
confidence: 99%
“…Specific emphasis is also laid on the manufacturing of spare parts from thermoplastic, thermosetting plastics, and short and continuous fibre-reinforced composites. In [9][10][11][12], the authors offer insights on some recent technological and environmental applications of reinforced polymers. In [13], the author noted that Menzolit BMC 3100 is a special material developed for the automotive industry to produce headlights.…”
Section: Introductionmentioning
confidence: 99%
“…As they are manufactured with a fixed production width, preforming usually leads to high scrap rates of up to 50%, [3][4][5][6] reducing economy and sustainability of the process and inducing the need of recycling of in-house scrap. 7 In addition, when aiming at highest performance of manufactured parts, loadrelated fiber orientations within the preform are necessary, which is not easy to achieve with two-dimensional semi-finished textile products and also further increases scrap rates. One possibility to overcome these drawbacks is using direct preforming technologies such as dry fiber placement (DFP), sometimes also referred to as automated dry fiber placement.…”
Section: Introductionmentioning
confidence: 99%